Pengaruh Kualitas Sistem Informasi, Kualitas Informasi dan Perceived Usefulness terhadap Kepuasan End User Software Akuntansi - Mubaraq, Muhammad Raihan; Trihatmoko, Huda (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
This study aims to provide empirical evidence regarding the effect of information system quality, information quality and perceived usefulness on the satisfaction of end-users of accounting software. Respondents in this study were 66 respondents in 30 SKPDs located in West Lombok Regency, West Nusa Tenggara (NTB) in the accounting division in the Regional Work Unit that is directly involved in the use of accounting software. Samples were selected using a purposive sampling technique. Data collection techniques in this study using a questionnaire or questionnaire with a semantic differential scale and analyzed using multiple linear regression. The results of this study indicate that the quality of information systems, the quality of information and perceived usefulness affect the satisfaction of end users of accounting software. Keywords: Information Systems Quality; Information Quality; Perceived Usefulness; End User Satisfaction.